The Use of TikTok Application on Learning English Speaking - Humairah, Andi Ananda; Mahmud, Murni; Amin, Fatimah Hidayahni (International Journal of Language, Education, and Literature, 2025)
This research is aimed to find out the students’ perception of using TikTok application in learning English Speaking and identify the impacts of using TikTok application for the students. This research focused on the students’ opinions to obtain data on their perception and response towards the implementation of TikTok in learning English speaking. The research subjects have been selected purposively with 6 students regarding their experiences learning English speaking using TikTok application. This research was conducted using interview questions as the instrument of the research. The researcher found that there was various thought of each student, mainly positive than negative. The positive view students perceived are unlimited sources, entertaining contents, accessible, improve their speaking skill, and various features. While the negative perception students concerned are age restriction, unfiltered content, algorithm, less efficient, limitation on the content and one-way interaction The impacts are divided into positive impact and negative impact. It was revealed that the students are able to improve their creativity using TikTok’s contents and obtaining an amount of knowledge in a short time. It is proven that TikTok has benefits for the students’ English learning improvement. Negatively, the impacts that are concerning to the research subjects are TikTok might leads students to addiction, get easily distracted by the contents, may leads to misleading information, and other social media alternative to learn English speaking.